2019
DOI: 10.24251/hicss.2019.214
|View full text |Cite
|
Sign up to set email alerts
|

Is Virtual Reality the Future of Learning? A Critical Reflection

Abstract: The year 2016 marks the so-called second wave of VR, which was initiated by the first consumer VR-HMD, Oculus Rift (development kit), entering the market. There are four practical advantages in the field of virtual reality learning: a shift from abstract to tangible settings, interactivity rather than passive observations, using desirable but practically infeasible methods, and breaking the bounds of reality. In contrast, current VR technologies also feature certain limitations. The most common negative factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…For instance, a Leap Motion would sense the hand of a user by a camera or a Manus VR glove uses integrated sensors within the glove to trigger finger and hand movements. Moreover, we suppose in accordance with existing literature [43,44,46,51], the perception of the virtual body as the own one will be increased by the stronger feeling of naturalness.…”
Section: Implications For Theory and Designsupporting
confidence: 74%
See 2 more Smart Citations
“…For instance, a Leap Motion would sense the hand of a user by a camera or a Manus VR glove uses integrated sensors within the glove to trigger finger and hand movements. Moreover, we suppose in accordance with existing literature [43,44,46,51], the perception of the virtual body as the own one will be increased by the stronger feeling of naturalness.…”
Section: Implications For Theory and Designsupporting
confidence: 74%
“…Overall, current VR technologies using HMDs aim at different research fields in order to enhance learning outcomes [e.g. 24,33,39,44,53], for better entertainments [47], or to improve healthcare solutions [e.g. 7,13,26,35,36].…”
Section: Implications For Theory and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, panoramic video in education and teaching has shortcomings. For example, Schwarze A found that panoramic video viewing equipment may cause motion sickness in learners, which prevents learners from focusing on the learning content ( Schwarze et al, 2019 ). The overly realistic and complex scenes in panoramic videos may distract learners’ attention to irrelevant content, leading them to be lost in the scenes, decreasing their interest in learning, decreasing their positive learning experience, and increasing their cognitive load, which ultimately reduces learners’ learning efficiency and affects their learning results ( Rong-Huai and Yang-JunY, 2012 ).…”
Section: Introductionmentioning
confidence: 99%